Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Let f(x) = x - 2 and g(x) = x2 - 7x - 9. Find f(g(-1)).

Sagot :

[tex]f(g(-1))=(-1)^2-7\cdot(-1)-9-2=1+7-11=-3[/tex]
luana
[tex]f(x)=x-2\\\\ g(x)=x^2-7x-9\\\\ f(g(-1)):\\ First\ calculate\ g(-1):\\\\ g(-1)=(-1)^2-7*(-1)-9=1+7-9=8-9=-1\\\\\ f(-1)=-1-2=-3\\\\ \boxed{f(g(-1))=-3}[/tex]